Very long chain fatty acid–inhibiting herbicides: Current uses, site of action, herbicide-resistant weeds, and future - Jhala, Amit J.; Singh, Mandeep; Shergill, Lovreet; Singh, Rishabh; Jugulam, Mithila; Riechers, Dean E.; Ganie, Zahoor A.; Selby, Thomas P.; Werle, Rodrigo; Norsworthy, Jason K. (Weed technology, 2024)
The herbicides that inhibit very-long-chain fatty acid (VLCFA) elongases are primarily used for residual weed control in corn, barley, oat, sorghum, soybean, sugarcane, certain vegetable crops, and wheat production fields in the United States. They act primarily by inhibiting shoot development of susceptible species, preventing weed emergence and growth. The objectives of this review were to summarize 1) the chemical family of VLCFA-inhibiting herbicides and their use in the United States, 2) the VLCFA biosynthesis in plants and their site of action, 3) VLCFA-inhibitor resistant weeds and their mechanism of resistance, and 4) the future of VLCFA-inhibiting herbicides. After their reclassification as Group 15 herbicides to include shoot growth-inhibiting herbicides (Group 8), the VLCFA-inhibiting herbicides are currently represented by eight chemical families (benzofurans, thiocarbamates, α-chloroacetamides, α-oxyacetamides, azolyl-carboxamides, isoxazolines, α-thioacetamides, and oxiranes). On average, VLCFA-inhibiting herbicides are applied once a year to both corn and soybean crops in the United States with acetochlor and S-metolachlor being the most used VLCFA-inhibiting herbicides in corn and soybean production, respectively. The site of action of Group 15 herbicides results from inhibition of the VLCFA synthase, which is encoded by several fatty acid elongase (FAE1)-like genes in VLCFA elongase complex in an endoplasmic reticulum. The VLCFA synthase is a condensing enzyme, and relies on a conserved, reactive cysteinyl sulfur in its active site that performs a nucleophilic attack on either the natural substrate (fatty acyl-CoA) or the herbicide. As of August 2023, 13 weed species have been documented to be resistant to VLCFA inhibitors, including 11 monocot weeds and two dicot weeds (Palmer amaranth and waterhemp). The isoxazolines (pyroxasulfone and fenoxasulfone) are the most recently (2014) discovered VLCFA-inhibiting herbicides. Although the intensity of VLCFA-inhibitor-directed discovery efforts has decreased over the past decade, this biochemical pathway remains a viable mechanistic target for the discovery of herbicide premixes and a valuable component of them. Nomenclature: Acetochlor; α-chloroacetamides; α-oxyacetamides; α-thioacetamides; azolyl-carboxamides; benzofurans; fenoxasulfone; isoxazolines; thiocarbamates; oxiranes; S-metolachlor; pyroxasulfone; Palmer amaranth, Amaranthus palmeri S. Watson; waterhemp, Amaranthus tuberculatus (Moq) J.D. Sauer; barley, Hordeum vulgare L.; corn, Zea mays L.; oat, Avena sativa L.; sorghum, Sorghum bicolor (L.) Moench; soybean, Glycine max L.; sugarcane, Saccharum officinarum L.; wheat, Triticum aestivum L.